2019
DOI: 10.1002/anie.201910659
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Citrulline 4‐Hydroxylase from Nonribosomal Peptide GE81112 Biosynthesis and Engineering of Its Substrate Specificity for the Chemoenzymatic Synthesis of Enduracididine

Abstract: The GE81112 tetrapeptides are a small family of unusual nonribosomal peptide congeners with potent inhibitory activity against prokaryotic translation initiation. With the exception of the 3‐hydroxy‐l‐pipecolic acid unit, little is known about the biosynthetic origins of the non‐proteinogenic amino acid monomers of the natural product family. Here, we elucidate the biogenesis of the 4‐hydroxy‐l‐citrulline unit and establish the role of an iron‐ and α‐ketoglutarate‐dependent enzyme (Fe/αKG) in the pathway. Homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…These enzymes were studied spectroscopically and kinetically and their substrate specificity tested. Recent studies on the nonheme iron enzyme GetI showed it to hydroxylate l ‐Arg at the C 4 ‐position, although it was not clear whether arginine is its natural substrate [7] . A similar situation was found in the ethylene forming enzyme that apart from catabolizing αKG into ethene and three CO 2 molecules, also appears to bind and activate an arginine residue but hydroxylate it at the C 5 ‐position [8] .…”
Section: Introductionmentioning
confidence: 94%
“…These enzymes were studied spectroscopically and kinetically and their substrate specificity tested. Recent studies on the nonheme iron enzyme GetI showed it to hydroxylate l ‐Arg at the C 4 ‐position, although it was not clear whether arginine is its natural substrate [7] . A similar situation was found in the ethylene forming enzyme that apart from catabolizing αKG into ethene and three CO 2 molecules, also appears to bind and activate an arginine residue but hydroxylate it at the C 5 ‐position [8] .…”
Section: Introductionmentioning
confidence: 94%
“…Between June and October of 2019, additional papers describing pathways to free-standing α-amino acids have appeared in the biosynthetic literature. For interested readers, these references are cited here without further description. …”
mentioning
confidence: 99%
“…In 2019, we determined that GetI functions as a citrulline-4-hydroxylase, instead of a chlorohistidine hydroxylase, and is probably responsible for the biosynthesis of the second monomer of all three GE81112s. 63 Furthermore, sequencebased rational mutagenesis identified a variant of GetI, containing four mutations away from wild-type, that exhibits a complete switch in substrate preference from citrulline to arginine. The functional characterization of GetI provided an opportunity to construct the first two amino acid monomers of GE81112 B1 chemoenzymatically.…”
Section: Chemoenzymatic Synthesis Of Ge81112 B1 and Related Analoguesmentioning
confidence: 99%